Cursos superiores de graduação tecnológica: estigma discriminatório? - Civalsci, Elaine de Lourdes (2012)
This study belongs to the research area teacher development of the Education and Curriculum Post-graduate Studies of the Pontifical Catholic University of São Paulo (PUC-SP). In the last years, we have been watching the accelerated growth in the offering of Techonology Graduate Courses by private Universities. This type of course belongs to Technology and Professional Education which was regulated only in 2004, through Decree 5154/04, although the course has started in the 60's at the the Federal Education System. The delay in the legislation consolidation led to students‟ mistrust on the course credibility, giving rise to this research. Thus, this study aims at investigating the discriminatory stigma on Techonology Graduate Courses in the following aspects: curriculum, legislation and labor market. In order to achieve the aim of this study, we have carried out a documental research on the legislation and curriculum of a Techonology Graduate Course and of a Bachelor‟s Degree Course at a private University in São Paulo, Brazil. We have also carried out a field research in organizations. The key findings of this study were the following: there is no evidence of discrimination in the legislation documentary analysis; the students have the right to both getting a Graduate Degree and carrying on their studies in Post-graduate courses. The curricula document analysis presented no evidence of discrimination, since the differences which exist in these forms of Graduation are inherent to the objectives of each Graduation course. Nevertheless, the field research that was conducted in eighteen organizations of the labor market and by means of a questionnaire with open and closed questions showed that the majority of the surveyed companies had restrictions on the quality of the course and on the students‟ education. Most of the surveyed companies stated that the technologists were hired for operational positions, whereas the National Catalog of Technology Graduate Courses of the Ministry of Education and Culture (MEC), in Management and Business, enables Graduate students to perform both operational and managerial functions. The research was relevant to the academic community and to society, indicating the need for further studies on the quality and on the identity of this type of course as it serves a significant portion of the population: the working class that invests in its education at private institutions of higher education